Legal Framework of Telemedicine in Indonesia: An Analysis of Data Protection, Patient Privacy, and Medical Personnel Liability in the Digital Age - Bob Wahyudin; Arie, Marthen; Irwansyah, Irwansyah; Sampurno Suwondo, Slamet; Rahman, Ali (Journal of Neonatal Surgery, 2025)
This research analyzes the legal framework of telemedicine in Indonesia with an emphasis on data protection, patient privacy, and the responsibility of medical personnel. The method used is normative legal research (doctrinal legal research), which examines legislation, academic literature, and court decisions related to telemedicine services. The results showed that Law Number 36 of 2009 on Health and Law Number 27 of 2022 on Personal Data Protection provide a legal basis for the regulation of digital health services. However, there is still a lack of specific regulations regarding the licensing process, supervision mechanism, and liability when medical negligence occurs in telemedicine services. In addition, the absence of a fully integrated legal tool creates ambiguity of responsibility among various stakeholders, including doctors, digital platforms, and internet service providers. Therefore, it is necessary to establish a special authority that can harmonize various sectoral regulations, as well as establish technical and ethical standards. The results of this study recommend affirmation of licensing procedures, periodic audit mechanisms, and education for health workers and the public to improve legal literacy and prevent privacy violations. Thus, telemedicine is expected to operate safely, effectively, and responsibly